2014
DOI: 10.17221/407/2014-pse
|View full text |Cite
|
Sign up to set email alerts
|

Influence of row covers on soil loss and plant growth in white cabbage cultivation

Abstract: Row covers are usually used to protect plants from insects and cold temperatures, and to accelerate plant growth. But they could also serve as an erosion control strategy. For this reason, fleece (FC) and net covers (NC) in white cabbage (Brassica oleracea convar. capitata (L.) Alef. var. capitata L. f. alba) cultivation were tested in a two-year field experiment to determine effects on soil erosion, plant growth and plant diseases. Soil loss under FC was reduced on average by 76% and under NC by 48% compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…From the hypothesised spatial distribution shown in Figure 2, n = 5 in Equation (3) because the inner circular area has a central diameter of 40 cm. By substituting Equations ( 6) and (7) into Equation (3), downslope splash erosion rate S d (g•m −2 ) is obtained as…”
Section: Model Application and Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…From the hypothesised spatial distribution shown in Figure 2, n = 5 in Equation (3) because the inner circular area has a central diameter of 40 cm. By substituting Equations ( 6) and (7) into Equation (3), downslope splash erosion rate S d (g•m −2 ) is obtained as…”
Section: Model Application and Validationmentioning
confidence: 99%
“…Splash erosion is directly caused by the kinetic energy of raindrops [4,5], which is an important parameter in erosion prediction models. Ground cover reduces soil erosion and surface flow on hillslope landscapes, and different vegetation conditions affect the occurrence and development of splash erosion [6][7][8][9]. The two parameters used to study and predict splash erosion are the detachment rate and probability density of splashed particles within a certain distance [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Soils worldwide, especially the rainforest soils in southeastern Brazil, have been contaminated as a result of civil, agricultural and industrial activities (VAMERALI et al 2010). Even though there is an urgent need for a knowledge-based effort, the information about the effect of with hydrocarbons, heavy metals, and other chemical substances of forest woody plants is not enough (ÜBELHÖR et al 2014;VILLACÍS et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…They found soil erosion rate was moderately increased under the acidic and alkaline conditions because the physical properties of soil were changed under different pH conditions: acidic conditions caused the aggregation of soil due to aluminum dissolution, whereas alkaline conditions weakened the connectivity between soil particles due to the repulsive force from the zeta potential. Additionally, many studies indicated the importance of vegetation to reduce the soil loss and runoff (Valentin et al 1999, Shi and Shao 2000, Nearing et al 2005, Übelhör et al 2014. Carrol and Tucker (2000) indicated the high risk of erosion on steeper gradients; however, the runoff and erosion can be reduced effectively due to the vegetation growth in the rehabilitation area of open-cut coal mine based on the field study.…”
mentioning
confidence: 99%